Association between the level of serum soluble ST2 and invasively measured aortic pulse pressure in patients undergoing coronary angiography. Issue 8 (February 2019) - Kim, Hack-Lyoung; Lee, Jung Pyo; Lim, Woo-Hyun; Seo, Jae-Bin; Zo, Joo-Hee; Kim, Myung-A; Kim, Sang-Hyun
Abstract : Abstract: Despite the well-documented value of ST2 in heart failure and myocardial infarction, the role of ST2 in vascular biology has not yet been well defined. This study was performed to investigate the association between serum soluble ST2 (sST2) and invasively measured aortic pulse pressure (APP). A total of 167 consecutive patients with suspected coronary artery disease (CAD) (65.1 ± 9.8 years; men, 65.9%) referred for invasive coronary angiography was prospectively enrolled. APP was measured at the ascending aorta with a pig-tail catheter, and arterial blood samples for the measurement of sST2 were collected before coronary angiography. Serum sST2 levels were quantified by radioimmunoassay. Most of the patients (73.9%) had significant CAD (stenosis ≥ 50%) on coronary angiography. Patients with higher APP (≥76 mmHg) showed a significantly higher sST2 level compared to those with lower APP (<76 mmHg) (31.7 ± 13.9 ng/mL vs 26.2 ± 10.2 ng/mL, P  < .001). In simple correlation analysis, there was a significant positive correlation between sST2 levels and APP ( r  = 0.413, P  < .001). In multiple linear regression analysis, sST2 had an independent association with APP even after controlling for potential confounders ( β  = 0.331, P  < .001). The serum sST2 level may be independently associated with invasively measured APP in patients undergoing coronary angiography. The result of this study gives insight into the role of sST2 in aortic stiffening, and suggests that the sST2 level may be a useful marker of aortic stiffness.